HUBUNGAN KEPATUHAN DENGAN PENGETAHUAN IBU MENGENAI PELAYANAN ANTENATAL DI WILAYAH KERJA PUSKESMAS JENDERAL URIP KOTA PONTIANAK - ., Ferdy Fikriadi (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background:Maternal mortality rate (MMR) is an indicator to measurematernal health. One of profince wich had high maternal mortality isKalimantan Barat. Maternal mortality can decreased by antenatal care visitcompliance however Jenderal Urip is a health service that has the lowestantenatal care visit in Pontianak City with 89,2% first visit and 88,94%forth visit.Objective: This research was aim to know the relationshipbetween antenatal care visit compliance with mothers level of knowledgeabout antenatal care in working area of Jenderal Urip Health Service inPontianak City.Method: This research is analitic with cross sectionaldesign and the population were mothers whom pregnant in 2011 that livedin working area of Jenderal Urip Health Service. The 85 number ofsamples were selected using a simple random sampling method. The datawas get by handing out the questionare and analized using KolmogorovSmirnovtest.Result:This research shows from 85 samples, 67 (78,82%) have a good compliance and 18 (21,18%) have low. Whereas 50 people (58,82%) have a good knowledge, 21 people (24,70%) moderate, and 14people (16,48%) have lowknowledge. Kolmogorov-Smirnov test show thatthere was significant relationship between those variable (p=0,001).Conclusion: There was significant relationship between antenatal carevisit compliance with mothers level of knowledge about antenatal care inworking area of Jenderal Urip Health Service in Pontianak City.Keywords: Compliance, knowledge level, antenatal care